Working papers 1-5 - Participatory Research Project (Canada) (1978, 1978)
This set of documents is designed to provide conceptual schemes for using participant involvement in social research as an essential method for adult education programmes - The first paper by Budd Hall and the third by Bonnie Cain deal with research methodology and show how participatory research differs fundamentally from current academic research. The second, 'Dene learning for self-determination' describes how minority groups in Arctic Canada achieved better understanding of community problems through taking part in a Federal inquiry into a projected oil pipe-line and were thus capable of social action. Another paper gives case studies from Botswana on the role of theatre arts in the process of problem solving at community level. A bibliography on participatory research forms one of the working papers.